Al-Akhţā’ Aş-Şautiyyah Fī Qirāati Al-Qurān Ladā Ţullābi Aş-Şaf Aś-Śāmin Fī Madrasati Al-Mutawassiţah Li Muassasati Tarbiyyati Aş-Şibyān Bi Sukābūmī: الأخطاء الصوتية في قراءة القرآن لدى طلاب الصف الثامن في مدرسة المتوسطة لمؤسسة تربية الصبيان بسوكابومي - Nasution, Nurmia; Aulyaa, Muhammad Habiibul; Mufarokah, Siti; Nandes, Rio (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
This research aims to identify the forms of phonological errors in reading the Qur’an among eighth-grade students in the junior hight school of the Boys’ at PUI YATSHI in Sukabumi. I used The researcher provides a qualitative introduction to the descriptive case study approach. The results of the research showed that there are three common types of phonetic errors, which are letter transposition, negligence in performing the adjective of the letter, and errors in the vowel. The factors that lead to these errors are divided into two parts: For internal factors and external factors. The internal factors are: the students’ unfamiliarity, the uniqueness of Arabic with some letters, the students’ leniency in vocal performance, their natural altruism, pedantry or exaggeration in eloquence, pronunciation defects, and the habit of reading incorrectly from the beginning of learning the Qur’an. The external factors are: Lack of a lesson in teaching the Holy Qur’an per week, lack of reading the Qur’an and training in correct reading, and lack of interest on the part of the family.